Rancang Bangun Solar Panel Tracker Dual Axis Berbasis Internet Of Things - Beda, Nadjamudin; Joni Eka Candra; Muhammad Jufri (LPPM-ITEBA, 2024)
The aim of this research is to develop a monitoring system for an IoT-based dual axis solar tracking system, with the aim of increasing the efficiency of light absorption by solar panels and monitoring the power produced by IoT-based solar panels. A tracking system is a method that is able to move solar panels according to changes in the direction of the light source, ensuring that the solar panels receive maximum light to achieve maximum power. The research method applied involves a series of tests to monitor the solar tracking system. Measurements involve the variable tilt of the solar panel, voltage, current and light intensity using a designed device, the results of which are then compared with standard measuring instruments. The system that has been developed successfully moves the solar panels according to the direction of the light source. The monitoring system uses Arduino and Esp8266 as microcontrollers, DinamoDC as the driving motor. After that, the percentage error for each measurement is calculated. The research results show that the light insensitivity values from solar panel test data were taken from 07.00 to 17.00. Based on several measurements that have been carried out, it can be concluded that the solar panels are functioning well, this is proven by the results of solar panel measurements with an average measured voltage of 18.45 volts – 20.38 volts.